Genetic evaluation of Ethiopian Boran cattle and their crosses with Holstein Friesian in central Ethiopia: reproductive traits - Haile, Aynalem; Joshi, B.K.; Ayalew, W.; Tegegne, Azage; Singh, A. (Cambridge University Press, 2009)
Breed additive and non-additive effects as well as genetic parameters for calving interval (CI), days open (DO), age at first service (AFS), age at first calving (AFC), number of services per first conception (NSC) and breeding efficiency (BE) were estimated in Ethiopian Boran cattle and their crosses with Holstein Friesian in central Ethiopia. The data analysed were spread over 15 years (1990–2004). The Ethiopian Boran cattle had longer CI and DO, lower BE and delayed AFS and AFC compared with all the crosses. However, there was no significant difference in NSC between the genetic groups. Comparison between the crosses revealed no clear cut superiority of any of the genetic groups except for CI and DO which were shorter for 0·50 and 0·875 crosses compared with the 0·75 crosses. The additive breed differences between Ethiopian Boran and Holstein Friesian for CI, DO, NSC and BE were not significant (P>0·05). These estimates are also associated with large standard errors. The non-significance of the otherwise large difference (40 days for CI for instance) between the two breeds could be a result of a large variation (and hence standard errors) associated with the traits. On the other hand, the estimates for additive direct effects for AFS and AFC were negative and significant (P<0·01). The estimates were −7±2·1 and −7±2·8 months, respectively. The individual heterosis values were not significant (P>0·05) for CI, DO, NSC and BE. However, significant (P<0·01) estimates for AFS and AFC (P<0·05) were recorded. None of the maternal heterotic effects for reproduction traits were significant (P>0·05) except for AFC, for which positive (2·9 months) and significant (P<0·05) estimates were obtained. Heritabilities of CI, DO, AFS, AFC, NSC and BE for crosses were 0·1±0·046, 0·1±0·047, 0·6±0·145, 0·7±0·159, 0·1±0·071 and 0·6±0·156, respectively. Selection coupled with improved herd reproductive management should substantially improve the reproductive performance of the indigenous Ethiopian Boran breed under such production system.